2019
DOI: 10.1111/gcb.14850
|View full text |Cite
|
Sign up to set email alerts
|

Divergent carbon cycle response of forest and grass‐dominated northern temperate ecosystems to record winter warming

Abstract: Northern temperate ecosystems are experiencing warmer and more variable winters, trends that are expected to continue into the foreseeable future. Despite this, most studies have focused on climate change impacts during the growing season, particularly when comparing responses across different vegetation cover types. Here we examined how a perennial grassland and adjacent mixed forest ecosystem in New Hampshire, United States, responded to a period of highly variable winters from 2014 through 2017 that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…However, increasing temperatures are also associated with higher rates of ecosystem respiration (Duveneck and Thompson 2017) and water use (Beamesderfer et al 2020) that can counteract increases in forest carbon uptake (e.g. Sanders-Demott et al 2020). Therefore, the future effects of longer growing seasons on ecosystem-level carbon and water cycling are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing temperatures are also associated with higher rates of ecosystem respiration (Duveneck and Thompson 2017) and water use (Beamesderfer et al 2020) that can counteract increases in forest carbon uptake (e.g. Sanders-Demott et al 2020). Therefore, the future effects of longer growing seasons on ecosystem-level carbon and water cycling are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The improved DNDC model predicted less CO 2 release rates during the late winter to early spring in 2016 at the forest. The high observed CO 2 release rates in this period were likely due to anomalously warm conditions in the winter of 2015/2016 (NOAA National Centers for Environmental Information, 2017) and relatively high temperature sensitivities of ecosystem respiration ( Q 10 ≈ 3.6 to 4.7) during the winter to spring period at the forest that led to warm soil conditions and high CO 2 release rates (Sanders‐DeMott et al, 2019). However, since DNDC integrated equations with lower temperature sensitivities for ecosystem respiration (Li et al, 1992a), the model predicted lower daily NEE values.…”
Section: Discussionmentioning
confidence: 99%
“…These field measurements provide an opportunity to evaluate the performance of the improved DNDC model for predicting both energy and CO 2 fluxes and to assess the radiative forcing of different land use types in the study region. The technical details regarding the measurements of energy fluxes and NEE, and the relevant auxiliary variables are described by Burakowski et al (2018) and Sanders‐DeMott et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, D' Arrigo et al (2004) reported a decline in the temperature sensitivity of tree growth during the late twentieth century, based on dendrochronological data. Research by Sanders-DeMott et al (2020) revealed that the strength of the correlation between vegetation productivity and temperature declined from the early 1980s to 2011 in the northern hemisphere. Moreover, other studies found unimodal relationship curves between vegetation and temperature (Duffy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%